2010
DOI: 10.1098/rspb.2009.2041
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal and X-linked single nucleotide polymorphisms reveal a steep Asian–Melanesian ancestry cline in eastern Indonesia and a sex bias in admixture rates

Abstract: The geographical region between mainland Asia and New Guinea is characterized by numerous small islands with isolated human populations. Phenotypically, groups in the west are similar to their neighbours in mainland Southeast Asia, eastern groups near New Guinea are similar to Melanesians, and intervening populations are intermediate in appearance. A long-standing question is whether this pattern primarily reflects mixing between groups with distinct origins or whether natural selection has shaped this range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 37 publications
4
76
0
3
Order By: Relevance
“…However, although female-biased patterns of admixture are observed in Malayo-Polynesian-speaking societies of eastern Indonesia (Cox et al 2010;Xu et al 2012), the general Philippine population is sex neutral in this respect (Cox et al 2010). Among Philippine negrito groups in northern Luzon, both male-and female-biased effective population sizes are observed (Heyer et al this issue).…”
Section: Gene Exchange In the Philippinesmentioning
confidence: 99%
“…However, although female-biased patterns of admixture are observed in Malayo-Polynesian-speaking societies of eastern Indonesia (Cox et al 2010;Xu et al 2012), the general Philippine population is sex neutral in this respect (Cox et al 2010). Among Philippine negrito groups in northern Luzon, both male-and female-biased effective population sizes are observed (Heyer et al this issue).…”
Section: Gene Exchange In the Philippinesmentioning
confidence: 99%
“…The movement of rice southeastwards through Indonesia eventually ceased owing to the presence of a resistant Papuan-speaking population, still dominant today in New Guinea, that had no interest in its adoption as a viable crop. The density and food-producing status of this indigenous population brought the Malayo-Polynesian migration to a linguistic and genetic standstill in the southeastern corner of Indonesia (Lansing et al 2011;Cox et al 2010;Karafet et al 2010). There is really no clear evidence at all for any migration of MalayoPolynesian-speaking populations from west to east in the vicinity of New Guinea, neither to its north nor to its south, and it is suggested here that they moved in the opposite direction, from the Bismarcks to Indonesia.…”
Section: Likewise Chamorro Is Normally Classified As a Westernmentioning
confidence: 99%
“…A previous estimate for admixture based on SNPs found that the Asian contribution to another group of Aeta was approximately 17% smaller for the X chromosome than for the autosomes, while balanced among the general Philippine population (Cox et al 2010). Although our own nuclear DNA data indicate different sex-specific behaviors between negrito populations, we only compare these groups to the general population using haploid loci.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that this sex-biased genetic admixture involving Austronesian women and Near Oceanic men was the result of the matrilineal structure and matrilocal residence pattern of Austronesian societies in the past (Jordan et al 2009;Lansing et al 2011). An exception to this global trend can be found in an Aeta group from the Luzon region of the Philippines, where X-chromosome admixture levels were significantly lower than those for the autosomes; in contrast, the non-negrito populations studied had balanced amounts of admixture (Cox et al 2010).…”
mentioning
confidence: 93%
See 1 more Smart Citation